Accelerating Li+ recovery kinetics of 5TiO2·2H2O adsorbents from original geothermal water by configuring TiO2·H2O phase - Lin Jing; Chunxi Hai; Xuemei Zuo; Lijuan Zhang; Shengde Dong; Yanxia Sun; Luxiang Ma; Qi Xu; Xin He; Yuan Zhou (Desalination, 2026)

Targeting Peroxiredoxin 6: Tannic Acid Inhibits Singapore Grouper Iridovirus Infection via PRDX6‐Dependent Pathway and Antioxidant Response - Xiangmou Qin; Chen‐Ao Li; Lin Huang; Qing Yu; Mingming Zhao; Yanxia Gao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; Junxiang Lai; Ermeng Yu; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a major viral pathogen threatening grouper aquaculture. The lack of specific antiviral drugs underscores the urgent need to develop safe and effective control strategies. This study demonstrates that tannic acid (TA) exhibits significant anti‐SGIV activity in vitro. In grouper spleen (GS) cells, TA inhibited SGIV replication in a concentration‐dependent manner. Time‐of‐addition assays confirmed its antiviral efficacy when applied either before or after SGIV infection. Mechanistically, TA directly interfered with SGIV particle infectivity, viral adsorption, entry and intracellular replication. Network pharmacology analysis suggested TA's targets are associated with host cellular antioxidant pathways, among which Peroxiredoxin 6 (PRDX6) was identified as a potential target of TA. Further experiments confirmed that TA upregulated the Nrf2 antioxidant pathway and suppressed the expression of pro‐inflammatory cytokines (IL‐1β, IL‐8). Notably, TA enhanced the expression of PRDX6, and overexpression of PRDX6 significantly inhibited SGIV replication, indicating that PRDX6 contributes to the antiviral effect of TA. In vivo, TA treatment not only restored PRDX6 expression in infected groupers but also significantly reduced viral load in liver and spleen following SGIV infection. These findings demonstrate that TA inhibits SGIV through direct viral interference and PRDX6‐mediated antioxidant modulation, highlighting its potential as a natural therapeutic agent against SGIV.

Comparative study on pollution characteristics and ecological risk in Xiangshan Bay and its adjacent eastern sea area - Yanxia Wang; Honglei Jiang; Shengwei Xu; Xuelei Wang; Weiliang Shen; Lin Huang; Haihang Wang; Yuan Sun (Marine Pollution Bulletin, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Enhancing electrocatalytic glycerol oxidation coupled with hydrogen production over single-atom ruthenium catalyst - Xiaoli Jiang; Jing Jiang; Yanxia Liu; Kaimin Deng; Lin Zhao; Zhaoling Ma; Huaiyi Ding; Yue Lin; Yagang Zhang (Chemical Engineering Journal, 2026)

Epigallocatechin Gallate (EGCG) Inhibits Singapore Grouper Iridovirus (SGIV) Infection by Interfering With Viral Life Cycle and Modulating Host Cell Cycle G2/M Checkpoint - Tianhong Zhao; Jinkun Xie; Chen‐Ao Li; Mingzhu Liu; Qing Yu; Lin Huang; Yanxia Gao; Mingming Zhao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a highly pathogenic virus that causes substantial economic losses in marine grouper aquaculture, and effective antiviral agents are currently lacking. In this study, the anti‐SGIV activity of epigallocatechin gallate (EGCG), a natural compound from green tea, was evaluated and its underlying mechanisms were investigated. Cytotoxicity assays showed that EGCG at concentrations up to 12.5 μg/mL was safe for grouper spleen (GS) cells. EGCG treatment reduced viral MCP and VP19 mRNA expression in a dose‐dependent manner, indicating its anti‐SGIV activity. Mechanistic studies revealed that EGCG directly impaired SGIV particle infectivity and interfered with viral adsorption, entry, and intracellular replication. Network pharmacology analysis identified overlapping genes between EGCG targets and SGIV‐induced differentially expressed genes, with enrichment pathways related to cell cycle regulation, particularly the G2/M checkpoint. Further studies showed that SGIV infection upregulated the G2/M checkpoint regulators WEE1 and CHEK2, and EGCG treatment reversed these dysregulations, suggesting that EGCG alleviates SGIV‐induced G2/M arrest. In vivo, EGCG treatment significantly reduced viral load in infected groupers and improved survival rate. Collectively, these findings demonstrate that EGCG exerts potent anti‐SGIV activity both in vitro and in vivo by directly targeting multiple steps of the viral life cycle and modulating host cell cycle G2/M checkpoint pathways, highlighting its potential as a natural therapeutic agent against SGIV infection.

Virus-host metabolic interaction: SGIV-induced protein lactylation suppresses viral propagation - Mingming Zhao; Jiaxi Li; Mingzhu Liu; Ying Pan; Sining Su; Xiangmou Qin; Yanxia Gao; Lin Huang; Junxiang Lai; Jia Cai; Huapu Chen; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Wind Hazard Analysis of Typhoons Approaching Coastal China Based on the Typhoon Size Data - Zhenghao Wen; Lin Xue; Zhaozheng Che; Rui Zhang; Yanxia Zhao (Journal of Meteorological Research, 2026)

In vitro and in vivo antiviral effects of myrcene on MSRV infection in largemouth bass (Micropterus salmoides) - Zhengzhao Liu; Lin Huang; Jieying Yu; Qing Yu; Mingzhu Liu; Yanxia Gao; Xiangmou Qin; Junxiang Lai; Fei Ling; Yanlei Chang; Shuyu Han; Jia Cai; et al. (Fish & Shellfish Immunology, 2026)

Paeoniae Radix Alba polysaccharides: Structural characterization, macrophage immunomodulation, and potent vaccine adjuvant activity - Ming Zhao; Yushi Wang; Ran Guan; Shiyue Qin; Guoqiu Li; Jiaqi Wang; Zhiye Wang; Junyan Shang; Lingyi Xu; Qingrui Lin; Yanxia Ding; Xiaodan Ma; et al. (Carbohydrate Polymers, 2026)

TLR5-mediated pathogenic bacteria defense and functional maintenance of Misgurnus anguillicaudatus ovary - Yali Wang; Mengzhen Wang; Yanxia Lin; Yunfan Han; Enping Chen; Xiaohua Xia (Aquaculture, 2026)

Study on the discovery of lung-descending herbs and bioactive constituents using TRP channel-functionalized screening - Bin Yu; Jiaye Tian; Zewen Wang; Liansheng Qiao; Yanxia Liu; Qun Li; Yue Ren; Yuezhong Zhu; Li Lin; Yanling Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Elevated salinity amplifies polyethylene microplastic-induced soil nitrous oxide emissions - Shiying Lin; Guoling Yang; Yanxia Zhang; Lihu Liu; Yongxiang Yu; Huaiying Yao (Journal of Hazardous Materials, 2025)

Online determination of elements in pure iron by non-weighing micro-reaction with inductively coupled plasma optical emission spectrometry - Dandan Su; Xuejing Shen; Jingyu Hu; Yunhai Jia; Haina Zhao; Yanxia Hou; Guowu Yang; Fei Lin; Haizhou Wang (Analytica Chimica Acta, 2025)

Research on Time–Frequency Joint Equalization Algorithm for Underwater Acoustic FBMC/OQAM Systems - Weimin Hou; Ming Zhang; Lin Yang; Yanxia Wang (Journal of Marine Science and Engineering, 2025)
This study focuses on the equalization problem of the filter bank multicarrier system based on offset quadrature amplitude modulation (FBMC/OQAM) in underwater acoustics and proposes an innovative joint time–frequency-domain equalization (JTFDE) algorithm. The algorithm combines frequency-domain Minimum Mean Square Error (MMSE) equalization with time-domain adaptive decision feedback equalization, effectively addressing the shortcomings of traditional single-domain equalization methods in terms of multipath interference suppression and time-varying channel tracking. By first using frequency-domain linear equalization to preliminarily eliminate multipath interference, and then combining it with time-domain Recursive Least Squares (RLS) adaptive decision feedback to further suppress residual interference, the system performance is significantly improved. The experimental results show that compared with existing single-domain equalization methods, this scheme reduces the bit error rate at the system receiver and enhances the system’s interference resistance.

Advances in Research on Soil-Borne Diseases of Medicinal Plants and Their Prevention and Control - Linghe Huang; Yanxia Huang; Sai Jiang; Zixian Zeng; Zhaoyang Tan; Huaxue Huang; Zhi Wang; Shunxiang Li; Dousheng Wu; Lin Jiang (Current Microbiology, 2025)

MCPA-Na exposure in aquatic systems: disruption of pathways and increased susceptibility to infection in fish - Yanxia Lin; Ran Shi; Mengzhen Wang; Yali Wang; Yunfan Han; Yongcui Ma; Liyin Li; Xiaohua Xia (Aquatic Toxicology, 2025)

SIRT1 Regulates Iron Metabolism to Attenuate β-Cell Dedifferentiation by Inhibiting FoxO1 Acetylation - Tingting Li; Rulin Ma; Wennv Tang; Yanxia Zheng; Siyi Lv; Yuxi Liu; Lin Wang; Yusong Ding (Biological Trace Element Research, 2025)

Identification of Chlortetracycline Hydrochloride as a Antibacterial Compound Against Pseudomonas syringae pv. tomato DC3000 Through Natural Products Library Screening - Lin Jiang; Linghe Huang; Yajing Wang; Jing Li; Zixian Zeng; Wenlong Yang; Sai Jiang; Dousheng Wu; Zhi Wang; Shunxiang Li; Yanxia Huang; Hong Pu (Current Microbiology, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

Chemical profiles and mechanisms insights into Liuwei Dihuang-based formulas in diabetic nephropathy treatment: An integrated transcriptomics with in vitro experiments - Yanxia Liu; Anlei Yuan; Zewen Wang; Shijie Bi; Zhenzhen Xu; Chaoqun Liu; Bin Yu; Jiaye Tian; Liansheng Qiao; Zhaozhou Lin; Jun Jia; Yanling Zhang (Food Bioscience, 2025)

Time-series InSAR reveals new insights into land subsidence in the Yellow River Delta, China - Yi Zhang; Ziliang Si; Xu Lin; Zehua Zhang; Hongxian Chu; Chang Cao; Yanxia Liu; Haijun Huang; Bingqi Huang; Zechao Bai; Kuifeng Wang; Xinghua Zhou; et al. (Marine Georesources & Geotechnology, 2025)

Antibacterial mechanisms of PLA on Aeromonas hydrophila and its application in fish disease resistance and fish preservation - Xiaohua Xia; Yanxia Lin; Yali Wang; Lu Qin; Shuang Liu; Hongwei Zhang; Xiaowen Zhang; Yi Li (Food Bioscience, 2025)

Parkin deficiency exacerbates particulate matter-induced injury by enhancing airway epithelial necroptosis - Yuting Lin; Meiyu Quan; Xibin Wang; Wanqi Miao; Haibo Xu; Baiqi He; Bin Liu; Yanxia Zhang; Yijing Chen; Binqian Zhou; Mengying Xu; Li Dong; et al. (Science of The Total Environment, 2024)

Optimizing carbonation reaction parameters of calcium carbide slag in acidic/alkaline environment enhancing CO2 mineralization efficiency - Zihe Pan; Lin Chen; Chunxia Cao; Fengjie Zhang; Huirong Zhang; Yanxia Guo (Chemical Engineering Journal, 2024)

Genome-wide identification of 9-cis-epoxy-carotenoid dioxygenases (NCEDs) and potential function of OfNCED4 in carotenoid biosynthesis of Osmanthus fragrans - Yanxia Du; Lin Peng; Bin Dong; Shiwei Zhong; Jinping Deng; Qiu Fang; Zheng Xiao; Yiguang Wang; Hongbo Zhao (Trees, 2024)

Does invasive submerged macrophyte diversity affect dissimilatory nitrate reduction processes in sediments with varying microplastics? - Xueyuan Gao; Xiaowei Li; Yingcai Wang; Cheng Lin; Yanxia Zuo; Xiaolu Li; Wei Xing (Journal of Hazardous Materials, 2024)

Late Cenozoic uplift of the Liupan Mountains: Evidence from the Neogene loess deposits - Zhilin He; Yansong Qiao; Zhengtang Guo; Chaoqin Chen; Long Chen; Yang Fu; Ye Yang; Yanxia Liang; Xinru Lin; Guoqiao Xiao; Tao Zhan (Science China Earth Sciences, 2024)

Impact of inherent calcium in coal on the structure and performance of activated carbon in flue gas activation: The enhanced mechanism of calcite on the methylene blue adsorption - Jian Niu; Lin Luo; Jinglei Cui; Huirong Zhang; Yanxia Guo; Linbo Li; Fangqin Cheng (Journal of Cleaner Production, 2023)

Correlation between tumor cell migration and formaldehyde levels revealed by fluorescence imaging - Wei Quan; Yanxia Li; Wenhui Song; Zihong Li; Qian Zhang; Weiying Lin (Chemical Engineering Journal, 2023)

Blood pressure states transitions among bus drivers: the application of multi-state Markov model - Yanxia Wu; Weigang Wu; Yeli Lin; Juan Xiong; Xujuan Zheng (International Archives of Occupational and Environmental Health, 2022)

MicroAlgal Biofilm Reactor (MABR) – Evaluation of Biomass Support Materials and Nitrate Removal Performance - Yanxia Lin; Agamemnon Koutsospyros; Washington Braida; Christos Christodoulatos; Amalia Terracciano; Tsan-Liang Su (Environmental Processes, 2022)

Assessing Oil Content of Microalgae Grown in Industrial Energetic-Laden Wastewater - Abhishek RoyChowdhury; Juliana Abraham; Tobi Abimbola; Yanxia Lin; Christos Christodoulatos; Adeniyi Lawal; Agamemnon Koutsospyros; Washington Braida (Environmental Processes, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)